Explorations in methodology - Massey, Alexander; Walford, Geoffrey (Studies in educational ethnography,, 1999)
The series as a whole recognises that the nature of ethnography is contested, and takes this to be a sign of its strength and vitality. This second volume in the series focuses on debates and developments in methodology and the many ways in which ethnographic work interacts with education. The contributions to this volume are diverse and challenging. They indicate that ethnography is a rich field that has much to offer the study of education. Particular chapters are concerned with access to research sites, critical ethnography, text construction, dilemmas of researching different ethnic groups and or researching children, the influence of the researcher, writing ethnography, ethno-drama, and the concept of triangulation.